Explaining SME performance with fsQCA: The role of entrepreneurial orientation, entrepreneur motivation, and opportunity perception - Rafał Kusa; Joanna Duda; Marcin Suder (Journal of Innovation & Knowledge (JIK), 2021)
Entrepreneurs, opportunities, and entrepreneurial behaviors play an important role within the theory of entrepreneurship. However, we have limited knowledge about possible associations among these factors. Therefore, this study investigates these interactions. The study aims to identify the combinations of entrepreneurship dimensions, entrepreneur motivation, and opportunity perception that lead to an increase in a firm's performance. This study focuses on the small and medium-sized enterprise (SME) sector, wherein the entrepreneurial spirit is dominant. It is based on a sample of 61 SMEs operating in the Lesser Poland region of Poland. The factor's combinations are identified with a fuzzy-set qualitative comparative analysis (fsQCA). The analysis reveals previously unknown combinations of the investigated factors leading to performance in SMEs, with varying roles depending on accompanying factors. Specifically, this study reveals the following combinations that lead to a firm's performance: opportunity openness with proactiveness, heterogeneity of motivation with innovativeness, and risk-taking with proactiveness. These observations highlight the role of combining various conditions to improve performance. This study's findings contribute to the entrepreneurship and SME literature by explaining the role of different combinations of factors in determining a firm's performance (including the motivations and opportunity perception of the entrepreneur). It also provides meaningful implications for entrepreneurs and managers, indicating combinations of factors that lead to an increase in firm performance, the role of the diversification of opportunities, and the importance of motivation differentiation.
Keywords: L22; L25; L26; M21; 650; Innovativeness; Motivation; Opportunity perception; Performance; Proactiveness; Risk-taking